Family Process and Peer Deviance Influences on Adolescent Aggression: Longitudinal Effects Across Early and Middle Adolescence - Buehler, Cheryl A. (2012)
Beginning in sixth grade at an average age of 11.9 years, 416 adolescents and their parents participated in 4 waves of data collection involving family observations and multiple-reporter assessments. Ecological theory and the process-person-context-time (PPCT) model guided the hypotheses and analyses. Lagged, growth curve models revealed that family hostility and peer deviance affiliation predicted adolescent aggression in the subsequent year. Family warmth played only a minor role in protecting against adolescent aggression. In hostile or low-warmth families, peer deviance affiliation linked to a declining aggression trajectory consistent with the arena of comfort hypothesis. The longitudinal findings suggest a nonadditive, synergistic interplay between family and peer contexts across time in adding nuance to understanding the adolescent aggression